The Main Problems and Directions of the Effective Development Tourism - SADYKOV, Zhassulan; ABDIKARIMOVA, Madina; GABDULINA, Ainur; MAKHASHEVA, Aigerim; TAKHTAEVA, Rimma; SAVANCHIYEVA, Armanay (Journal of Environmental Management and Tourism; Vol 9 No 6 (2018): JEMT Volume IX Issue 6(30) Fall 2018DO - 10.14505//jemt.v9.6(30).11, 2019)
This article notes that the prospect of one of the export-oriented industries in the Republic of Kazakhstan may be inbound tourism, since it was he who successfully developed in a crisis and provided support to other sectors of the economy. At present, the Kazakhstan tourism market is in the stage of active formation and formation. It is highlighted that the peculiarities of the formation of the international tourism market, its interdependence from other spheres of economic activity are not yet sufficiently studied and do not have certain well-established development trends. Indicators of the competitiveness of tourism in Kazakhstan in terms of indices of sustainable development of tourism, the dynamics of inbound tourist flow to Kazakhstan from CIS countries and other non-CIS countries for 2013-2017, indicators of the use of locations in the Republic of Kazakhstan for 2013-2017 are given. Proposals are made for the direction of effective development of tourism in the Republic of Kazakhstan by assessing the impact of international tourism on the socio-economic system of Kazakhstan.